Modification of a Double Adsorber Series Type with Multiple Stages Installed on Biodigester for Biogas Purification - Riski Gunawan Nasution; Rehan Aditya Nugraha; Desniorita Desniorita; Dyah Nirmala; Riski Gunawan Nasution (Politeknik Negeri Semarang, 2026)
Biogas produced from conventional biodigesters typically still contains impurities such as H₂S and CO, which can damage equipment and reduce combustion efficiency. This study aims to modify the adsorber into a series-type double adsorber integrated directly into the biodigester and evaluate its performance in purifying biogas. The study used a 200 L biodigester with 40 kg of cow rumen and 120 L of water. The fermentation process lasted 14 days with feed circulation. Purification was carried out using activated carbon as an adsorbent with a contact time of 60 minutes. Tested parameters included CH₄, H₂S, CO, O₂ levels, flame test, and FTIR characterization. The results showed that the double adsorber increased methane content from 69% to 91% and reduced H₂S to 0.7 ppm and CO to 0 ppm. The tool efficiency averaged above 90% for H₂S and CO absorption. The flame test showed an increased burning duration from 55 seconds to 1 minute 54 seconds. FTIR characterization confirmed the presence of O-H and C=O groups involved in the adsorption process. In conclusion, the series-type double adsorber modification is effective in improving biogas quality according to SNI 8019:2014.